Virus Traffic of Pandemic: Integrative Science Perspective - Peribadi Peribadi; Samsul Samsul; Muhammad Arsyad; Juhaepa Juhaepa; Sarpin Sarpin; La Ode Montasir (Institut Agama Islam Negeri (IAIN) Kendari, 2020)
This paper aims to narrate ontological status in the context of empiric and metaphysic realisms as the integral and interdependent paradigms through Karl Raimun Popper's version of deductive phenomenology approach.The existence of pandemic virus not only booms greatly mysteriously that is strongly worrying about the life of contemporary society, but also results in various kinds of prejudices and imaginative, sensual, and intellectual-spiritual perceptions. As a result, it is essential to be discussed from the integrative science perspective.Key Words: Traffic, Ontology, Covid 19 and Pandemy